2011
DOI: 10.1007/s10265-011-0462-6
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the putative Ca2+-permeable mechanosensitive channels, NtMCA1 and NtMCA2, in Ca2+ uptake, Ca2+-dependent cell proliferation and mechanical stress-induced gene expression in tobacco (Nicotiana tabacum) BY-2 cells

Abstract: To gain insight into the cellular functions of the mid1-complementing activity (MCA) family proteins, encoding putative Ca²⁺-permeable mechanosensitive channels, we isolated two MCA homologs of tobacco (Nicotiana tabacum) BY-2 cells, named NtMCA1 and NtMCA2. NtMCA1 and NtMCA2 partially complemented the lethality and Ca²⁺ uptake defects of yeast mutants lacking mechanosensitive Ca²⁺ channel components. Furthermore, in yeast cells overexpressing NtMCA1 and NtMCA2, the hypo-osmotic shock-induced Ca²⁺ influx was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 55 publications
1
47
0
Order By: Relevance
“…Most recently, homologous genes in tobacco and rice, NtMCA1, NtMCA2 and OsMCA1, respectively, were identified; they are localized in the plasma membrane, channel Ca 2+ , and may have potential roles in cell proliferation. 16,17 However, direct evidence for mechanical stress-dependent activation of MCA proteins is still lacking.…”
Section: Et Al Reported That Msl9 and Msl10 Arementioning
confidence: 99%
“…Most recently, homologous genes in tobacco and rice, NtMCA1, NtMCA2 and OsMCA1, respectively, were identified; they are localized in the plasma membrane, channel Ca 2+ , and may have potential roles in cell proliferation. 16,17 However, direct evidence for mechanical stress-dependent activation of MCA proteins is still lacking.…”
Section: Et Al Reported That Msl9 and Msl10 Arementioning
confidence: 99%
“…[22][23][24] FM4-64 was used as a VM marker. 23,25 When GFP alone was expressed, it is localized to the nucleus and the cytoplasm (Fig.…”
Section: Intracellular Localization and Physiological Function Of A Rmentioning
confidence: 99%
“…The Arabidopsis MCA1 was identified by its ability to complement the low Ca 2+ and related lethality phenotypes of mid1 (mating induced death1) yeast mutants upon mating induction (Iida et al, 1994;Fischer et al, 1997;Nakagawa et al, 2007;Yamanaka et al, 2010;Kurusu et al, 2012aKurusu et al, , 2012c. Mid is a putative regulatory subunit of a high-affinity, low-capacity Ca 2+ influx system that has Cch1 as the putative pore-forming subunit (Iida et al, 1994;Fischer et al, 1997;Muller et al, 2001;Rigamonti et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Mid is a putative regulatory subunit of a high-affinity, low-capacity Ca 2+ influx system that has Cch1 as the putative pore-forming subunit (Iida et al, 1994;Fischer et al, 1997;Muller et al, 2001;Rigamonti et al, 2015). Interestingly, cch1 lethality was also partially complemented by MCA expression (Yamanaka et al, 2010;Kurusu et al, 2012aKurusu et al, , 2012c. Experiments in various cell types showed that overexpression of MCAs leads to increased Ca 2+ uptake under normal and membrane-distorting conditions (Nakano et al, 2011;Kurusu et al, 2012aKurusu et al, , 2012bKurusu et al, , 2012cFuruichi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation